Christian democracy and the fall of Communism - Gehler, Michael; Kosicki, Piotr H.; Wohnout, Helmut (2019)
Debates on the role of Christian Democracy in Central and Eastern Europe too often remain strongly tied to national historiographies. With the edited collection the contributing authors aim to reconstruct Christian Democracy?s role in the fall of Communism from a bird's-eye perspective by covering the entire region and by taking 'third-way' options in the broader political imaginary of late-Cold War Europe into account. The book's twelve chapters present the most recent insights on this topic and connect scholarship on the Iron Curtain?s collapse with scholarship on political Catholicism.0'Christian Democracy and the Fall of Communism' offers the reader a two-fold perspective. The first approach examines the efforts undertaken by Western European actors who wanted to foster or support Christian Democratic initiatives in Central and Eastern Europe. The second approach is devoted to the (re-)emergence of homegrown Christian Democratic formations in the 1980s and 1990s. One of the volume?s seminal contributions lies in its documentation of the decisive role that Christian Democracy played in supporting the political and anti-political forces that engineered the collapse of Communism from within between 1989 and 1991